BALANCING CARBON BUDGET IN CITIES IN INDIA - Choudhary, Kiran; Verma, Neha; Saini, Robin Kumar; Jaiswal, Poonam (International Journal of Engineering Science Technologies, 2025)
In India, significant increase in carbon dioxide level particularly in urban areas presents a critical concern, majorly driven by urbanization, industrial activities, and increased vehicle usage ultimately imposing severe health risks for the population. Major cities like Delhi, Mumbai, and Kolkata report CO2 concentrations exceeding safe threshold, emphasizing the need for effective carbon management strategies. Approximately 31% of India's population which resides in urban areas currently consumes around 70% of its total primary energy supply and is projected to expand significantly by 2050, making sustainable energy management a crucial task. Several government initiatives, such as the Smart Cities Mission, Atal Mission, and various national policies, aim to mitigate emissions and promote carbon neutrality by investing in renewable energy and enhancing urban infrastructure. In addition, successful local initiatives highlight the potential for cities to lead in the global effort against climate change. Despite some challenges like funding gaps and community resistance, there are numerous opportunities for implementing carbon reduction strategies through establishing public-private collaborations and building up community engagement, ultimately achieving India's goal of reducing its carbon emissions for a sustainable future.